MIDDLE INCOME TRAP DALAM PERSPEKTIF MAKROEKONOMI : STUDI KASUS DI INDOENSIA - Supriadi, Apip (Jurnal Ekonomi Kuantitatif Terapan, 2022)
The purpose of this study is to determine and analyze i) the condition of per capita income in Indonesia seen from the criteria of the Middle income trap and ii) the influence of exports, foreign investment and population, either partially or jointly on per capita income. The data used is secondary data for the period 1991 – 2000, with the analysis tool using multiple regression analysis. The results showed that the development of per capita income was included in the low er -middle income category. Furthermore, foreign investment, population and exports have a significant effect on per capita income.